Genotypic characterisation of monepantel resistance in historical and newly derived field strains of Teladorsagia circumcincta. (December 2019) - Turnbull, Frank; Devaney, Eileen; Morrison, Alison A.; Laing, Roz; Bartley, Dave J.
Abstract: Recent reports of monepantel (MPTL) resistance in UK field isolates of Teladorsagia circumcincta has highlighted the need for a better understanding of the mechanism of MPTL-resistance in order to preserve its anthelmintic efficacy in this economically important species. Nine discrete populations of T. circumcincta were genotypically characterised; three MPTL-susceptible isolates, three experimentally selected MPTL-resistant strains and three field derived populations. Full-length Tci-mptl-1 gene sequences were generated and comparisons between the MPTL-susceptible isolates, MPTL-resistant strains and one field isolate, showed that different putative MPTL-resistance conferring mutations were present in different resistant isolates. Truncated forms of the Tci-mptl-1 gene were also observed. The genetic variability of individual larvae, within and between populations, was examined using microsatellite analyses at 10 'neutral' loci (presumed to be unaffected by MPTL). Results confirmed that there was little background genetic variation between the populations, global F ST <0.038. Polymorphisms present in exons 7 and 8 of Tci-mptl-1 enabled genotyping of individual larvae. A reduction in the number of genotypes was observed in all MPTL-resistant strains compared to the MPTL-susceptible strains that they were derived from, suggesting there was purifying selection at Tci-mptl-1 as a result of MPTL-treatment. The potential link between benzimidazole (BZ)-resistance and MPTL-resistance was examined by screening individual larvae for the presence of three SNPs associated with BZ-resistance in the β-tubulin isotype-1 gene. The majority of larvae were BZ-susceptible homozygotes at positions 167 and 198. Increased heterozygosity at position 200 was observed in the MPTL-resistant strains compared to their respective MPTL-susceptible population. There was no decrease in the occurrence of BZ-resistant genotypes in larvae from each population. These differences, in light of the purifying selection at this locus in all MPTL-resistant isolates, suggests that Tci-mptl-1 confers MPTL-resistance in T. circumcincta, as in Haemonchus contortus, but that different mutations in Tci-mptl-1 can confer resistance in different populations. Graphical abstract: Image 1 Highlights: Different null mutations of Tci-mptl-1 are present in monepantel resistant strains. Microsatellite analysis showed little divergence between UK Teladorsagia isolates. Tci-mptl-1 appears to be under purifying selection after monepantel administration. These findings are consistent with monepantel-resistance in Haemonchus. Monepantel treatment may select against benzimidazole-resistance.